Edukasi Akupresure Nyeri Haid pada Remaja - Fadilah, Amelia Nur; Wahyuni, Sri; Br. Nainggolan, Julita; Donela, Ardenia; Isfaizah (Universitas Ngudi Waluyo, 2024)
Problems often felt by female adolescents related to menstruation are dysmenorrhea and premenstrual syndrome. Dysmenorrhea is menstruation accompanied by pain. The impacts caused by dysmenorrhea are pain, abdominal cramps, headaches, discomfort and impaired concentration. One effort to deal with dysmenorrhea pain is to use a non-pharmacological method, namely acupressure. The purpose of this activity is to increase adolescent knowledge about acupressure therapy to reduce menstrual pain. Community Service will be carried out in 3 stages, namely the First Stage is to prepare by collaborating with partners. The Second Stage is to provide counseling on menstrual pain acupressure, using Projector media and teaching menstrual pain acupressure techniques. The Third Stage is to conduct an evaluation by giving post-test questions. From the results of Community Service, it was found that before the counseling, the majority of adolescent knowledge levels were in the poor category, namely 14 people (70%), and after the counseling, the adolescent knowledge level was in the good category, namely 20 people (100%). This shows that there was an increase in adolescent knowledge before and after counseling. It is hoped that health workers can increase health promotion with media that is interesting and easy to understand for teenagers to increase knowledge about reproductive health. Abstrak Masalah yang sering dirasakan remaja wanita berkaitan dengan menstruasi adalah dismenore dan sindrom premenstruasi. Dismenore yaitu menstruasi yang disertai dengan rasa nyeri. Dampak yang ditimbulkan dari disminore adalah nyeri, kram perut, sakit kepala, ketidaknyamanan dan gangguan kosentrasi. Salah satu upaya untuk menangani nyeri disminore dengan menggunakan metode nonfarmakologi yaitu akupresure. Tujuan kegiatan ini adalah meningkatkan pengetahuan remaja mengenai terapi akupresure untuk mengurangi nyeri haid. Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan kerja sama dengan mitra. Tahap Kedua Memberikan penyuluhan mengenai akupresure nyeri haid, menggunakan media ppt dan mengajarkan teknik akupresure nyeri haid. Tahap Ketiga Melakukan evaluasi dengan cara memberikan soal posttest. Dari hasil pengabdian Masyarakat didapatkan bahwa sebelum dilakukan penyuluhan, sebagian besar tingkat pengetahuan remaja dalam kategori kurang yaitu 14 orang (70%), dan sesudah penyuluhan tingkat pengetahuan remaja dalam kategori baik yaitu 20 orang (100%). Hal ini menunjukkan bahwa terjadi peningkatan pengetahuan remaja sebelum dan sesudah penyuluhan. Diharapkan tenaga kesehatan dapat meningkatkan promosi kesehatan dengan media yang menarik dan mudah dipahami kepada remaja untuk meningkatakn pengetahuan mengenai kesehatan reproduksi.